Buzzing before the Storms: infodemic pattern of COVID-19 in Indonesia - Arina Rubyasih; Stefani Made Ayu Artharini Koesanto; Arifah Bintarti; Jackson Pasini Mairing (Penerbit Universiti Kebangsaan Malaysia, 2023)
Amid the COVID-19 pandemic that Indonesia has been facing as a country with diversity and a high population, hoaxes and misinformation have become an acute problem. The Ministry of Communication and Informatics recorded 1,600 hoaxes related to COVID-19 from January 2020 to June 2021. By using the concept of infodemic and the theory of uses and gratification, this research attempt to describe and analyze categories of fake news, the types of media used, the description of the issues raised in the fake news, and the frequency of hoaxes spread during the COVID-19 pandemic in Indonesia; and examine the relationship between the number of new COVID-19 cases and the frequency of hoaxes in the early days of the pandemic. This study used quantitative methods, with trend analysis in data processing of 1970 hoax issues released by the Ministry of Communication and Informatics to the number of new cases of COVID-19 patients during the same time frame. The results show no relationship between total COVID-19 cases and real issues. The frequency pattern of hoax issue distribution during the COVID-19 pandemic follows infodemic conditions, with the peak of hoax circulation equal to the start of COVID-19 cases in Indonesia. Although the Indonesia government has made various efforts to address the problem of hoaxes and misinformation during the COVID-19 pandemic in Indonesia, this research shows that further action is still required to reduce the negative impact of hoaxes and misinformation on Indonesian society.